Stigmasterol from Eichhornia crassipes (Water Hyacinth): Isolation, Characterization and X-ray Structure - S. Singh, Keisham; G. Sawant, Sneha; Devi, Prabha; Kaminsky, Werner (Asian Journal of Chemistry, 2015)
Chemical investigation of Eichhornia crassipes (water hyacinth) collected from the back waters of Kochin, southern India lead to isolation of an oxygenated sterol, stigmasterol (1). The molecular formula of 1 was determined to be C29H48O by combination of NMR and mass spectroscopic data. The sterol was fully characterized by FTIR, NMR (1H and 13C) and mass spectral data. Solid state structure of the sterol was determined by single crystal X-ray diffraction. The compound crystalizes in the chiral monoclinic space group P21 with a solution optical rotation [a]D = -35° (c 0.16, CHCl3).